Optimizing estradiol level for gonadotrophin-releasing hormone antagonist initiation among patients with simple tubal factor infertility - Wang, Yizhuo; Xu, Xiuhua; Yang, Ai-min; Zhang, Jie; Luo, Zhuo-ye; Han, Yan; Cui, Na; Li, Qian; Shi, Baojun; Zhao, Zhi-ming; Hao, Gui-min (Frontiers in Endocrinology, 2022)
Objective: To investigate the optimal estradiol (E2) level on the day of GnRH-ant initiation in order to maximize the clinical pregnancy rate (CPR) after fresh embryo transfer among patients with simple tubal factor infertility. Methods: A retrospective cohort study was conducted in the Reproductive Medicine Center, the Second Hospital of Hebei Medical University. A total of 1493 IVF-ET cycles of patients diagnosed with single tubal factor infertility from August 2016 to August 2021 were included and equally allocated into five distinct groups according to the quintile serum E2 levels on the day of GnRH-ant initiation. The five groups had similar baseline data except for antral follicle count. Result(s): The serum E2 level on GnRH-ant initiation day was determined as an independent predictor of clinical pregnancy after adjusting for confounding factors such as age, infertility duration, body mass index, cycle number, antral follicle count and the number of transferred embryos. Through smooth curve fitting, we found that with the increase of serum E2 levels on the day of GnRH-ant initiation, CPR showed a trend of slight increase and then slight decrease. The maximal CPR was achieved when the serum E2 level on GnRH-ant initiation day was 498 pg/ml. When E2 was less than 498 pg/ml, the OR of clinical pregnancy was 1.05 (95%CI: 1.00, 1.11, P=0.0583). When E2 was greater than 498 pg/ml, the OR of clinical pregnancy was 0.97 (95%CI: 0.95, 0.98, P=0.0003). Furthermore, CPR remained high when E2 was 436.8-658.6 pg/ml, but declined significantly by more than 40% when E2 was ≥ 894.4 pg/ml (P＜0.05). Conclusion(s): Serum E2 level should be considered as an adjuvant parameter for GnRH-ant initiation. The best E2 value was 498 pg/ml, and GnRH-ant administration could be recommended to initiate when serum E2 was 436.8-658.6 pg/ml. If GnRH-ant was initiated when serum E2 was above 894.4 pg/ml, the CPR after fresh embryo transfer may decline dramatically and thus cancellation of fresh embryo transfer and earlier initiation of GnRH-ant in future cycles should be considered.